A portable versus micro‐Raman equipment comparison for gemmological purposes: the case of sapphires and their imitations1. (20th July 2014) - Barone, Germana; Bersani, Danilo; Crupi, Vincenza; Longo, Francesca; Longobardo, Ugo; Lottici, Pier Paolo; Aliatis, Irene; Majolino, Domenico; Mazzoleni, Paolo; Raneri, Simona; Venuti, Valentina; Ropret, Polonca; et al.
<x xml:space="preserve">Abstract</x> In the last decade, Raman spectroscopy has been used for routine investigation for gemmological purposes, being non‐destructive and non‐invasive. In addition, this technique grants short measurement times without any sample preparation. In this context, this work is focused on the spectroscopic characterization of different kinds of blue gems, including sapphires, by comparing the performance of a handheld Raman instrumentation along with a micro‐Raman spectrometer, with the aim to provide gemmological certification and to get information on the provenance of the gems. The main goal of the present study is to identify imitation gems and to distinguish between natural and synthetic sapphire; in this latter case, micro‐Raman measurements were fundamental for the characterization of the inclusions. Moreover, the chemical composition of blue gems has been obtained by portable XRF technique. The obtained data show that a portable Raman spectrometer can be recommended as a fast and easy instrument to discriminate sapphire from imitations. Copyright © 2014 John Wiley & Sons, Ltd.